Pronombre o adjetivo demostrativo o este… marcador del discurso: El uso del marcador del discurso este en el español de México - Mayr, Paul; Harjus, Jannis (Linguistik Online, 2024)
This paper aims to present observations on the pragmaticalized use as well as the concomitant functions of the demonstrative este in Mexican Spanish. Este seems to serve an additional range of functions in Mexican Spanish in particular, but also in other Hispanic American varieties, as it has turned into a quite productive discourse marker that can be considered, among other things, as a hesitation element, an outline signal, and probably also as an evidentiality marker. The specific functional domains (especially with regard to possible evidential functions) will be illustrated in more detail in the paper using oral language data from the speaker community of the southern Mexican city of Oaxaca de Juárez. The study also includes a sociolinguistically oriented quantitative analysis, the results of which will also be discussed in the context of language ideological attitudes towards este.